A Reason Action Theory: Factors Impacting Male Students' Motivation to Quit Smoking - Mutia Rahma Fauzia; Diyah Yulistika Handayani (Proceedings Series on Health & Medical Sciences, 2022)
Background: Smoking behavior is often found in our society. Based on the results Basic Health Research of Indonesia, it is reported that the proportion of male and female smokers in Indonesia is 64.9% and 2.1%, respectively. Smoking has been shown to cause various health problems and increase risk factors for death. This study uses a quantitative method with a cross-sectional approach. The population was male students of the Faculty of Engineering and Science at Universitas Muhammadiyah. The samples were 300 students. Afterward, they filled out questionnaire adopted from Istifaizah that have been distributed using the WhatsApp group. The data were analyzed using the Chi-Square test. The result showed that the significance value of the relationship between attitudes and motivation to quit smoking was 0.000?0.05. Meanwhile, the significance value of the relationship between subjective norms and motivation to quit smoking was 0.000?0.05. Afterward, the significance value of the relationship between perception and motivation to quit smoking was 0.000?0.05. Respondents attitudes, subjective norms and perceptions toward smoking cessation showed that the percentage of positive attitudes was lower than the percentage of negative attitudes. The respondents' motivation to quit smoking showed that the percentage of motivation to quit smoking was low more than the high motivation to quit.